Revision of the genus Poriptus Stal (Hemiptera: Heteroptera: Pentatomidae: Pentatominae) - Barcellos, Aline; Grazia, Jocelia (Zootaxa, 2008)
The neotropical genus Poriptus Stål, 1861 is revised, based upon morphological characters. Poriptus tobago sp. nov. is described from the Caribbean. Illustrations and a key to species are provided.